Omitting vitamin and trace mineral premixes, and(or) reducing inorganic phosphorus during late finishing did not affect growth performance, carcass traits, or muscle quality - Mavromichalis, I.; Kropf, Donald H.; Kennedy, G.A.; Hines, Robert H.; Senne, B.W.; Kim, I.H.; Johnson, S.L.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Omitting the vitamin and trace mineralpremixes and(or) adding 2/3 less supplementalinorganic phosphorus source (from .55% down to .40% total P) to diets during late finishing (191 to 265 lb) had no effect ongrowth performance, carcass characteristics, or muscle quality in high-lean pigs. Thus, this concept can be used to decrease the cost of feeding terminal-cross pigs to heavy weights, while decreasing excretion of minerals from intensive swine operations.
Keywords: Swine; Finishing pigs; Vitamins; Minerals; Phosphorus; Muscle quality